The Role of Muslim Religious Leaders in Mental Health: A Community-Based Participatory Research Study in the San Francisco Bay Area - Humam, Fairuziana (Pastoral psychology, 2023)
Muslim religious leaders provide guidance to their communities on social and spiritual aspects of life. Previous studies suggest that religious leaders (imams) may also offer counseling and mental health support for Muslims. Research has not investigated the extent to which Muslims rely on religious leaders to fulfill this role. This study explores the perceptions of Muslims in the San Francisco Bay Area, California, regarding the role of religious leaders in mental health care. The study utilizes a community based participatory research approach. A total of 40 participants across four demographic groups (male community members, female community members, young adult community members, and religious leaders) were recruited to participate in focus group discussions. Participants were given six case scenarios illustrating various mental health problems and asked to share their thoughts regarding the role of religious leaders in the management of each case. Focus groups were audio recorded, transcribed, and analyzed using thematic analysis. The themes included participants’ expectations of religious leaders' qualifications and limitations as well as the perceived distinction between a religious leader and a mental health professional. The findings of this study provide insights into Muslims' perceptions of the roles that religious leaders play in mental health.